PERILAKU PASIEN DIABETES MELITUS DALAM UPAYA PENCEGAHAN KAKI DIABETIK - I Nyoman Sejana; Komang Agus Jerry Widyanata; V.M Endang Sri Purwadmi Rahayu; I Ketut Dira (Jurnal Kesehatan Medika Udayana, 2018)
Background: Diabetes Mellitus is a disease with high levels of glucose (simple sugar) in the high blood because the body can not release or use insulin adequately. One complication that is feared by people with Diabetes is Diabetic Foot or Diabetic Gangrene. This research aims to determine the behavior of patients with diabetes mellitus in the prevention of diabetic foot in room of Sahadeva and Nakula Sanjiwani Gianyar District Hospital. Methods: Types of research used in this research is descriptive survey approach. Sample of the study are 40 patients with diabetes mellitus hospitalized in the room of Sahadeva and Nakula Sanjiwani Gianyar District Hospital using consecutive sampling technique. Data is collected in the period March to May 2012 by filling out a questionnaire about behavioral prevention of diabetic foot. Results: The results of data analysis showed that the behavior of patients with Diabetes Mellitus in the prevention of Diabetic Foot based on education level, age, gender and occupation. From the 40 respondents there were: 55% of the level of knowledge good, 80% good attitude, 70% good actions and 67,5% good actions in the category of good behavior. Conclusion: It can be concluded that the behavior of patients with Diabetes Mellitus in the prevention of Diabetic Foot is in a good category with the factors assessed including knowledge, attitudes, and actions.Keywords : Diabetes mellitus; diabetic foot; behavioral